On the theory of the third-order equation with multiple characteristics containing the second time derivative - Apakov, Yu. P.; Dzhuraev, T. D. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We construct a fundamental solution of the third-order equation with multiple characteristics containing the second time derivative, establish the estimates valid for large values of the argument, and study some properties of fundamental solutions necessary for the solution of boundary-value problems.